Structural and spectroscopic investigation of 1-acetyl-2-(4-ethoxy-3-methoxyphenyl) cyclopropane and its NLO activity - D.P. Lydia Renj; R. Racil Jeya Geetha; J. Jeni James; M. Amalanathan; M. Sony Michael Mary; Zoran Ratković; Jovana Muškinja (Chemical Physics Impact, 2024)
To identify promising compounds and to develop a potent non-linear optical material, the molecule 1-acetyl-2-(4-ethoxy-3-methoxyphenyl) cyclopropane (AEMC) was selected. FTIR and FT-Raman spectroscopy techniques were employed to predict the functional groups and vibrational modes of AEMC. Gaussian 09 W software was utilised to analyse the parameters of the optimised title compound. Reactive sites were forecasted using MEP plots. To clarify the chemical significance of the molecule, ELF and LOL are utilised. Furthermore, the presence of interactions within the molecule is confirmed by RDG analysis. The strong and weak hydrogen bonds between the non-bonding atoms of AEMC are studied with the aid of AIM analysis. Additionally, the material's capacity to produce non-linear effects (NLO) was ascertained by examining the linear polarizability and first order hyper polarizability values.